Pictorial Floristic Diversity of Grasses and Associated Vegetation from Three Grasslands of Randhikpur Forest Range, Dahod, Gujarat - Tyagi Amee Padhiar, S. N.; Albert, Susy; Pandya, Neeta; Dhara, Gandhi; Panchal, Krishna (Indian Forester, 2010)
Floristic diversity of grasses and other associated herbaceous flora mainly the legumes was analyzed in three major forest sites occurring in Randhikpur range of Limkheda Taluka in Dahod district of Gujarat state. The study was with a view to asses the vegetation and suggest management strategy for speeding up the tree forms in the area. The area had low floral diversity in the premonsoon mainly because livestock rearing was the main resources of livelihood which has brought about the over-exploitation of the existing vegetations, which were less, both in number and abundance. In the post monsoon these areas possessed around forty four different species. At the three sites, among the grasses Heteropogon contortus Var. contortus Subvar. genuisus, Heteropogon contortus Var. contortus Subvar. typicus, Themeda triandra and Apluda mutica appeared to be dominant.